Detection of colour vision abnormalities in uncomplicated type 1 diabetic patients with angiographically normal retinas. - Hardy, K J (Br J Ophthalmol, 1992)
Colour vision function was assessed in 38 non-complicated type 1 diabetic patients in whom fluorescein angiography was normal, and was compared with that in 36 age-matched, non-diabetic controls. All of the patients were healthy and none were taking medication except insulin. The eye examination, which was normal in every patient, included the Ishihara and City University tests, measurement of Snellen acuity, slit-lamp examination, tonometry, and fundal photography as well as fluorescein angiography. Colour discrimination ability was measured with the Farnsworth-Munsell 100-hue test. Mean (SE) 100-hue test error score for the diabetic group was 86.8 (8.1) compared with 28.2 (3.3) for controls, p<<0.001. There was no relation between colour vision abnormalities and diabetes duration (r = 0, p>0.05), blood glucose at the time the colour tests were performed (r = 0.4, p > 0.05), most recent glycated haemoglobin result (r = 0.3, p>0.05), or the mean of all previous glycated haemoglobin results (r = 0, p>0.05). It is concluded that colour discrimination may be abnormal in uncomplicated type 1 diabetic patients before the onset of retinopathy, and that colour discrimination losses in diabetes may not be of vascular aetiology.